Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.7 - Simplifying Complex Fractions - Exercise Set: 34

Answer

$\dfrac{2+\dfrac{6}{x}}{1-\dfrac{9}{x^{2}}}=\dfrac{2x}{x-3}$

Work Step by Step

$\dfrac{2+\dfrac{6}{x}}{1-\dfrac{9}{x^{2}}}$ Evaluate the sum indicated in the numerator and the substraction indicated in the denominator: $\dfrac{2+\dfrac{6}{x}}{1-\dfrac{9}{x^{2}}}=\dfrac{\dfrac{2x+6}{x}}{\dfrac{x^{2}-9}{x^{2}}}=...$ Evaluate the division: $...=\dfrac{2x+6}{x}\div\dfrac{x^{2}-9}{x^{2}}=\dfrac{x^{2}(2x+6)}{x(x^{2}-9)}=...$ Take out common factor $2$ from the parentheses in the numerator and factor the parentheses in the denominator. After that, simplify: $...=\dfrac{2x^{2}(x+3)}{x(x-3)(x+3)}=\dfrac{2x^{2}}{x(x-3)}=\dfrac{2x}{x-3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.